Effects of gut microbiota on leptin expression and body weight are lessened by high-fat diet in mice. Issue 4 (26th March 2020) - Yao, Hongyang; Fan, Chaonan; Fan, Xiuqin; Lu, Yuanyuan; Wang, Yuanyuan; Wang, Rui; Tang, Tiantian; Qi, Kemin
Abstract: Aberration in leptin expression is one of the most frequent features in the onset and progression of obesity, but the underlying mechanisms are still unclear and need to be clarified. This study investigated the effects of the absence of gut microbiota on body weight and the expression and promoter methylation of the leptin. Male C57 BL/6 J germ-free (GF) and conventional (CV) mice (aged 4–5 weeks) were fed either a normal-fat diet (NFD) or a high-fat diet (HFD) for 16 weeks. Six to eight mice from each group, at 15 weeks, were administered exogenous leptin for 7 d. Leptin expression and body weight gain in GF mice were increased by NFD with more CpG sites hypermethylated at the leptin promoter, whereas there was no change with HFD, compared with CV mice. Adipose or hepatic expression of genes associated with fat synthesis ( Acc1, Fas and Srebp-1c ), hydrolysis and oxidation ( Atgl, Cpt1a, Cpt1c, Ppar-α and Pgc-1α ) was lower, and hypothalamus expression of Pomc and Socs3 was higher in GF mice than levels in CV mice, particularly with NFD feeding. Exogenous leptin reduced body weight in both types of mice, with a greater effect on CV mice with NFD. Adipose Lep-R expression was up-regulated, and hepatic Fas and hypothalamic Socs3 were down-regulated in both types of mice. Expression of fat hydrolysis and oxidative genes ( Atgl, Hsl, Cpt1a, Cpt1c, Ppar-α and Pgc-1α ) was up-regulated in CV mice. Therefore, the effects of gut microbiota on the leptin expression and body weight were affected by dietary fat intake.